Perspectives of melatonin usage in prophylaxis and treatment of postmenopausal osteoporosis - Kos-Kudła, Beata; Marek, Bogdan; Kajdaniuk, Dariusz; Wołowska, Kinga; Ostrowska, Zofia (Menopause Review/Przegląd Menopauzalny, 2003)
Pathogenesis of osteoporosis is complicated, multifactorial, and is still not fully recognized. Results of below presented study suggest that among factors determining pathogenesis of this disease, not only estrogen deficiency in postmenopausal period and many other well known hormonal, growth, immunological factors but also melatonin deficiency plays a substantial role. Many of recently published studies demonstrated that increased melatonin production may have protective effect against loss of bone mass in postmenopausal period. We postulated that administration of melatonin could have a beneficial effect in prophylaxis and treatment of postmenopausal osteoporosis.